Who broke Lincoln's thumb? - Roy, Ron, 1940-; Bush, Timothy (New York : Random House, 2005)
When they discover that one of the thumbs has been broken off the statue in the Lincoln Memorial, KC and Marshall set out to learn what happened and restore the thumb before a ceremony honoring the sculptor.
"A Stepping Stone Book."
RL: 2.8.
006-009.
630
Accelerated Reader AR
Keywords: Lost and found possessions -- Fiction; Lincoln Memorial (Washington, D.C.) -- Fiction; Statues -- Fiction; Mystery and detective stories; Washington (D.C.) -- Fiction